Pediatric pleural empyema: one of the management challenges in children of Democratic Republic of Congo - Kibwe Alphonse Simbi; Valentin Kazadi; Louis-Marie Aissi; François Mbahewaka Katsuva; Numbi Oscar Luboya; Léon Tshilolo; Vincenzo Zanardo (PAGEPress Publications, 2017)
Empyema is a serious complication characterized by purulent exudate and bacteria in the pleural space, which may progress to necrosis, cavitations or fistulas in the thoracic cavity. It remains a major challenge throughout low-income countries. Objectives were to emphasize the role of basic medical and radiologic approach and to resolve a severe lung complication when facilities are inadequate. A five-year-old female was referred with distress respiratory to the Emergency Unit of Monkole, a large public-private missionary hospital in Kinshasa, Congo. Chest X-ray showed a massive empyema that was resolved by immediate drainage and antibiotiocs. Results were rapid improvement and discharge after 3 weeks. A classic medical and imaging approach is a winning return in low-income countries. According to the British Thoracic Society guidelines, pleural effusion with compromising respiratory function can be managed by drainage and antibiotics.